Learning Purposive Communication: A Personal Narrative Experience of Non-Teacher Education Students - Salendab, Fahad Abdul; Laguda, Jorge Loja (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This research explored the learning experiences of non-teacher education students enrolled in Purposive Communication at Sultan Kudarat State University-Kalamansig Campus. The study employed a qualitative design and non-probability purposive sampling. This study included six(6) non-teacher education students participants, such as students taking BS in Information Technology, BS in Biology, and BS in Fisheries. For data collection and collection, a semi-structured interview guide question was used. Colizzi’s thematic analysis was employed to analyze the data. The learning experiences of non-teacher education students in purposive communication revealed that they enjoyed learning Purposive communication through hybrid learning. Various performance tasks were provided for the students to perform, and these tasks are based on real-life experience. In performing these tasks, English was evident as a medium of instruction. Non-teacher education students can integrate responsive examples in the community and the global arena. Further, the most common challenges experienced by non-teacher education students were technical issues, distractions, time management, understanding course expectations, lack of in-person interaction, adapting to unfamiliar technology, and uncertainty about the future. It is recommended that the institution implement a monitoring strategy that would sustain the teaching methods employed by the teachers to make the teaching-learning process effective and productive in Purposive communication. The institution must provide sound-based classroom management during the new normal education and religiously implement hybrid learning to maintain the learning process. The institution should provide learning tools for poor but deserving non-teacher education students to assist them in learning Purposive communication even in times of educational crisis.